Inaugural dating violence awareness week : a communication campaign to raise awareness of dating violence. - Lee, Carmen Jia Min. (2009)
The authors of this Final Year Project report collaborated with a specialised counselling centre for interpersonal violence, the Centre for Promoting Alternatives to Violence (PAVe), to plan and actualise a public communication campaign.